(3cJGH GdeaQhVGJs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUGHF, CHh GdMSf, (B289 (3g` s
(3ChdgG (B:s
(3hgj SJi hKdKhf TcdkG jRjO Cf GdeKdK RhGjI C H L GdbGFeI eJSGhi GdCVdGY hefUa RGhjI s
(3BNQgG (B:s
(3jbhd aGdbSWQ eYdhe hGdbSeGf eYdheGf hPdc eG CQOfGg Je cJGH GdeaQhVGJ s
(3Vef eLehY , JQJjHgG (B: (3GdJGSYs
(3GfXQ eY GdeNWhW Qbe (B66s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B270s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(9 / 2432) s
Keywords: (3GdQjGVjGJs